Bio‐Based Aliphatic Polyurethanes Through ADMET Polymerization in Bulk and Green Solvent. Issue 4 (13th December 2013) - Lebarbé, Thomas; More, Arvind Sudhakar; Sane, Prakash Sudhir; Grau, Etienne; Alfos, Carine; Cramail, Henri; Lutz, J.‐F.; Sumerlin, B.; Matyjaszewski, K.
<x xml:space="preserve">Abstract</x> A new route to α, ω‐diene urethane monomer is proposed by converting 10‐undecenoic acid into the corresponding acyl azide, followed by urethanization with 10‐undecenol. ADMET polymerizations of this α, ω‐diene urethane monomer as well as other bio‐based α, ω‐dienes bearing various organic functions (ester, carbonate, ether, amide) were carried out in bulk and solution conditions. A screening of the most commonly used metathesis catalysts allows to evaluate their tolerance toward the urethane function as well as toward Polarclean, a "green" and nontoxic high boiling point solvent. The influence of the nature of the central organic function in these α, ω‐diene monomers on the thermomechanical properties is investigated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>